Collection analysis - Sami Kerzel (Linn-Benton Community College, 2015)
The purpose of this collection analysis is to ensure the Linn-Benton Community College (LBCC) Library’s collection meets the needs of their patrons by providing reliable and up-to-date materials, representing a variety of opinions. This analysis will provide insight into the Library’s physical collection. While academic libraries are typically less interested in the age of the material or their circulation, and more interested in significant, in-depth materials, smaller libraries tend to be more focused on the usefulness of their collection.